PENGARUH STRES KERJA TERHADAP KEPUASAN KERJA PEGAWAI DINAS PERTANIAN KOTA BIMA - Fidiyatun Anggriani; Yusuf, Muhammad; Jaenab (Jurnal Nusa Manajemen, 2024)
This study aims to determine the Effect of Job Stress on Employee Job Satisfaction at the Bima City Agriculture Service. The approach used in the study is an associative approach. The population in the study was 102 people with a sample of 60 people. Data collection techniques used were observation, questionnaires, and literature studies. The data analysis technique used in this study was a simple linear regression analysis technique which was assisted by the Statistical Product and Service Solution (SPSS) version 20 program. The results of the study showed that job stress had a significant effect on employee job satisfaction at the Bima City Agriculture Service.